PENINGKATAN HASIL BELAJAR KOGNITIF IPA FISIKA SISWA MELALUI PENERAPAN MODEL PEMBELAJARAN PENCAPAIAN KONSEP DIKELAS VII SMP IT MADANI SCHOOL - Ramadhan, Putra Ramadhan; Ma’aruf, Zuhdi Ma’aruf; ', Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study for to determine the increase in cognitive science learning outcomes through the application of the model physics student achievement in class VII SMP concept IT Madani School. This study was carried out in class VII SMP IT Madani School Pekanbaru in April to June 2015 by using a static design with two groups that applied to two homogeneous classes. Subjects consisted of 21 students in each class. The result showed that the score of the class that implements the model pembelajarn attainment of a higher concept than the final score classes that implement conventional learning models. At 5 measured variables that the average absorption capacity, the effectiveness of learning, mastery learning classical, individual completeness and thoroughness of the subject matter found that classes with the application of the concept model of learning achievement of the final score increase when compared to the conventional classroom learning model. Standard deviation is the implementation class model of learning achievement value concept is smaller than the conventional classroom learning model. Of variables measured, concluded that the achievement of the concept of learning model can improve learning outcomes of cognitive science of physics students. Key word : Concept Attainment Mode, Increase in Cognitive Study